Facial expression recognition using deep learning techniques / Aznal Anas Azlan and Muhamad Arif Hashim - Azlan, Aznal Anas; Hashim, Muhamad Arif (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Human’s feelings can be judged by their face expressions. Face expressions, in general, are a natural and direct way for humans to communicate their emotions and intentions. Trying to recognize the expression on a human face using devices is very difficult. Main objective of this research is to recognize several kinds of human face expression by implementing Convolutional Neural Network (CNN) technique in the facial expression recognition system. The system will display the result of the expression made by the user. The expressions that will be detected are “angry”, “disgusted”, “fearful”, “happy”, “neutral”, “sad”, and “surprised”. In conclusion, this research successfully developed a working facial expression recognition (FER) system with a high accuracy result.